Immune aging, dysmetabolism, and inflammation in neurological diseases - Deleidi, Michela; Jäggle, Madeline; Rubino, Graziella (Frontiers in Neuroscience, 2015)
As we age, the immune system undergoes a process of senescence accompanied by the increased production of proinflammatory cytokines, a chronic subclinical condition named as "inflammaging". Emerging evidence from human and experimental models suggest that immune senescence also affects the central nervous system and promotes neuronal dysfunction, especially within susceptible neuronal populations. In this review we discuss the potential role of immune ageing, inflammation and metabolic derangements in neurological diseases. The discovery of novel therapeutic strategies targeting age-linked inflammation may promote healthy brain aging and the treatment of neurodegenerative as well as neuropsychiatric disorders.